Answer :

(x + 5)

^{ 2 }– 36 = 0

(x + 5)

^{ 2 }– 6

^{ 2 }= 0

Using a ^{ 2 } – b ^{ 2 } = (a – b)(a + b)

(x + 5 – 6)(x + 5 + 6) = 0

(x – 1)(x + 11) = 0

x = 1, –11

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Draw the graph ofNCERT - Mathematics